Cyberbullying Analysis on WhatsApp Messenger Using the National Institute of Justice (NIJ) Method - Putra, I Putu Denny Indra; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
Social media is no stranger to today's digital era. Many people prefer to use social media because of its simplicity and safety, This is what makes social media more popular than other services. However, because of its convenience and security, social media, especially WhatsApp Messenger, are vulnerable to crime, one of the most common is cyberbullying.  For this reason, a mobile forensic investigation is required to find evidence related to cyberbullying. In this study, the National Institute of Justice (NIJ) method was used to investigate the WhatsApp Messenger platform used for cyberbullying. The NIJ method has 5 (five) stages to carry out the forensic process, namely Preparing, Collection, Examination, Analysis, and Reporting. This study also uses 3 assistance from software, namely MOBILedit Forensic, DB Browser for SQLite, and Odin3. This research is expected to be able to help solve the problem of cyberbullying and other crimes found on social media, especially WhatsApp Messenger.